1993
DOI: 10.1111/j.1365-2605.1993.tb01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in testicular function after endotoxin injection in the boar

Abstract: Twelve mature boars were injected intravenously with endotoxin from Salmonella typhimurium. Blood plasma was analysed for 15-ketodihydro-PGF2 alpha, LH and testosterone. The boars were castrated at various times after endotoxin administration and the testes examined by light and electron microscopy. The levels of 15-ketodihydro-PGF2 alpha and LH rose immediately after endotoxin injection followed by an increase in testosterone levels, and in five boars a second increase in LH levels was observed. Morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
3
23
0
1
Order By: Relevance
“…Serum IL-2 level also showed a marked increase in LPS-treated rats. These data are in harmony with the previous studies which revealed that infection and inflammation after administration of bacterial LPS lead to inhibition of testicular steroidogenesis and disruption of spermatogenesis in animals treated with LPS9,33 or with septic agents that generate LPS 18. Moreover, it has been reported that LPS administration resulted in the disruption of the blood-testis barrier and increased infiltration of white blood cells (WBCs) with subsequent production of ROS and activation of NO synthase 12.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Serum IL-2 level also showed a marked increase in LPS-treated rats. These data are in harmony with the previous studies which revealed that infection and inflammation after administration of bacterial LPS lead to inhibition of testicular steroidogenesis and disruption of spermatogenesis in animals treated with LPS9,33 or with septic agents that generate LPS 18. Moreover, it has been reported that LPS administration resulted in the disruption of the blood-testis barrier and increased infiltration of white blood cells (WBCs) with subsequent production of ROS and activation of NO synthase 12.…”
Section: Discussionsupporting
confidence: 90%
“…It has been established that a condition similar to infection can be produced in vivo by administration of bacterial LPS. In that regard LPS administration was found to inhibit testicular steroidogenesis and the disruption of spermatogenesis in animals 9. Cytokines are good candidates for involvement in the local control exerted between germ and Sertoli cell activity 10.…”
Section: Introductionmentioning
confidence: 98%
“…Infection and inflammation can be reproduced in vivo by administration of bacterial lipopolysaccharides (LPS), and several studies have observed inhibition of testicular steroidogenesis and disruption of spermatogenesis in animals treated with LPS (4,5) or with septic agents that generate LPS (6). Studies in mice using relatively high doses of LPS in vivo have demonstrated that Leydig cell steroidogenesis is inhibited via reduced synthesis of the cholesterol transport protein, steroidogenic acute regulatory protein (StAR), and of the steroidogenic enzymes, cholesterol side-chain cleavage enzyme, 17␣-hydroxylase/C 17,20 -lyase, and 3␤-hydroxysteroid dehydrogenase within several hours after injection (7)(8)(9).…”
mentioning
confidence: 99%
“…Several laboratories, including our own, have investigated this process using animal models of inflammation induced by injections of lipopolysaccharide (LPS), a bacterial outer cell wall molecule that activates the inflammatory functions of monocytes and macrophages (Wallgren et al 1993, Refojo et al 1998, O'Bryan et al 2000. Inhibition of both anterior pituitary secretion of luteinizing hormone (LH) and Leydig cell testosterone secretion have been observed in these models.…”
Section: Introductionmentioning
confidence: 99%